2010
DOI: 10.1159/000274974
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Duck Enteritis Virus <i>US6, US7</i> and <i>US8</i> Gene

Abstract: Aims: Duck enteritis virus (DEV) is a member of the family Herpesviridae, the genome of which is not completely analyzed. In order to provide further insights into the genomic organization, we decided to amplify the unknown sequence in the US region since three key glycoproteins are coded in this region. Glycoprotein D encoded by US6 gene is essential for virus entry and plays an important role in protecting animals from lethal challenge. Glycoprotein I and E encoded by US7 and US8 gene are required for cell-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(14 reference statements)
0
4
1
Order By: Relevance
“…Another report showed that the LORF11 gene of the VAC strain is located at the leftmost end of the DEV genome, and that the LORF11 gene encoded a putative protein of 275 amino acids in the VAC strain [14]; both of these results differ from our previous results [12]. Meanwhile, several genes in the US region have also been reported [15-18]; however, the length of the putative proteins encoded by the US10 gene and US7 gene has been debated. In this study, we present a fragment of 42,897 bp, which contains one end of the L region that includes part of the LORF11 gene, which was absent from the published VAC strain, and the whole of the DEV S region.…”
Section: Introductioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Another report showed that the LORF11 gene of the VAC strain is located at the leftmost end of the DEV genome, and that the LORF11 gene encoded a putative protein of 275 amino acids in the VAC strain [14]; both of these results differ from our previous results [12]. Meanwhile, several genes in the US region have also been reported [15-18]; however, the length of the putative proteins encoded by the US10 gene and US7 gene has been debated. In this study, we present a fragment of 42,897 bp, which contains one end of the L region that includes part of the LORF11 gene, which was absent from the published VAC strain, and the whole of the DEV S region.…”
Section: Introductioncontrasting
confidence: 75%
“…It has been reported that DEV also contains linear, double-stranded DNA, and its genome was shown to be approximately 180 kb in size, with a G plus C content of 64.3% [7]. Genomic sequences of DEV have been reported recently by several Chinese research groups; however, discrepancies were found among these reports [8-18]. Genes in the UL region of DEV and their arrangement have been reported by our laboratory, and the results generally showed more similarity with Mardiviruses [8-13].…”
Section: Introductionmentioning
confidence: 99%
“…To date, only the kinetics of expression and intracellular location of pUL24 [4], pUL31 [5,6], pUL51 [7,8], pUS3 [9], and dUTPase [10] have been investigated. Using bioinformatic tools, some putative glycoproteins and enzymes of the virus were characterized, such as gC [11], gE [12], gI, gD [13], and helicase pUL5 [14]. The identity of other components remains obscure.…”
Section: Resultsmentioning
confidence: 99%
“…The open reading frames (ORFs) and corresponding amino acid sequences of the three sHSPs were predicted using EditSeq software (Zhao & Wang, 2010). The identity of deduced amino acid sequences was determined using BioEdit software (Hall, 1999).…”
Section: Methodsmentioning
confidence: 99%